Digital Ethnopedagogy in Sociology Learning: Effects on Students’ Local Cultural Awareness and Multicultural Competence - Rizka Fadilla; Wilodati Wilodati; Siti Komariah (Jurnal Pendidikan Progresif, 2026)
This study aims to analyze the effect of digital ethnopedagogy on students' local cultural awareness and multicultural competence, and to examine the role of integrating local culture and digital technology in the development of these outcomes. This study uses a quasi-experimental pretest-posttest non-equivalent control group design. The study subjects consisted of 67 grade XI students, divided into an experimental group (n = 34) and a control group (n = 33). The experimental group followed a Project-Based Learning approach integrated with digital ethnopedagogy, while the control group followed Project-Based Learning (PjBL) without digital ethnopedagogy integration. Data were collected using instruments for local cultural awareness and multicultural competency. Data analysis was carried out using Multivariate Analysis of Covariance (MANCOVA), followed by Analysis of Covariance (ANCOVA), with pretest scores as a covariate. The results of the multivariate analysis showed that digital ethnopedagogy-based learning had a significant influence on students' local cultural awareness and multicultural competence (Wilks’ Λ = 0.724, F(2, 62) = 11.836, p < 0.001, partial η² = 0.28). Univariate analysis showed that treatment had a significant effect on local cultural awareness (F(1, 64) = 21.656, p < 0.001; η²p = 0.23) and multicultural (F(1, 64) = 14.342, p < 0.001, η²p = 0.19). Digital ethnopedagogy-based sociology learning has a positive effect on students' local cultural awareness and multicultural competence. The integration of local culture and digital technology within the framework of Project-Based Learning can serve as a contextual learning strategy to strengthen students' understanding of cultural identity and increase sensitivity to social diversity. Keywords: digital ethnopedagogy, sociology learning, local cultural awareness, multicultural competence.